Analysis of referee in-game interactions with players and other officials in professional Rugby Union - Lewis, M.; McNicholas, E.; McCarthy, A.-M.; Sherwin, I. (International Journal of Performance Analysis in Sport, 2023)
This study utilises qualitative methods to explore the behaviours of rugby union referees in order to inform the development of a pedagogical tool that can be used to develop communication of rugby union referees. Effective communication is a critical part of a rugby union referee`s performance, yet there is a dearth of literature surrounding this area of rugby union referee development. Participants included professional IRFU referees (n = 6) with experience both at domestic league levels as well as at an international level. Audio footage from professional games (n = 18) was analysed and transcribed verbatim. Raw quotes were categorised as meaning units and a total of nine communicative behaviours were devised: (1) Preventative Instruction, (2) Command, (3) Explanation, (4) Organisational, (5) Acknowledgement, (6) Game Management, (7) Informative, and (8) Consultation. Results reveal various types of key communicative behaviours employed by rugby union referees throughout a game, depending on the situation presented in front of them. The findings of this study reveal the importance of selecting the most effective type of communication in any given situation. Uncovering such behaviours will enhance the development and assessment of rugby union communication skills through a pedagogical framework in order to improve on-field performance.